2020
DOI: 10.1007/s00464-020-07621-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical adhesion score (CLAS): development of a novel clinical score for adhesion-related complications in abdominal and pelvic surgery

Abstract: Background Adhesions are a major cause of long-term postsurgical complications in abdominal and pelvic surgery. Existing adhesion scores primarily measure morphological characteristics of adhesions that do not necessarily correlate with morbidity. The aim of this study was to develop a clinical adhesion score (CLAS) measuring overall clinical morbidity of adhesion-related complications in abdominal and pelvic surgery. Methods An international Delph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…To the best of our knowledge, there have been no other studies or case reports describing this condition. It has been described that the formation of adhesions after abdominal surgery is relatively common, and 63-97% of patients develop adhesions after abdominal or pelvic surgery; general surgery, gynaecological and urological surgery (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have been no other studies or case reports describing this condition. It has been described that the formation of adhesions after abdominal surgery is relatively common, and 63-97% of patients develop adhesions after abdominal or pelvic surgery; general surgery, gynaecological and urological surgery (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Other Authors [24] have developed a novel clinical score for adhesion-related complications in abdominal and pelvic surgery: Clinical adhesion score (CLAS). This score includes outcomes and weight factors, describing the morbidity or clinical consequences of each adhesion-related complication: small bowel obstruction, difficulties at reoperation, female infertility, and chronic abdominal pain.…”
Section: Adhesions Scorementioning
confidence: 99%
“…For example, some of the reported classifications include only surgeryrelated events or are even more specific (eg, anastomotic leak or adhesiolysis-related events). 7,23 However, in complex visceral surgery, anesthesia is a relevant part of the operative process and comprises human factors with the potential for safety threats. 24 The classification of visceral surgery developed by Kaafarani et al includes only surgical adverse events and found an incidence of 0.02% for intraoperative adverse events and 31% for postoperative adverse events in a large group of 9,000 patients who underwent abdominal surgery.…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%